Cathodic corrosion: Part 1. Mechanism of corrosion via formation of metal anions in aqueous medium - Yanson, Yu.I.; Yanson, A.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
In this paper we describe an unusual electrochemical phenomenon, namely cathodic corrosion of platinum. We show that all existing models of cathodic corrosion are inconsistent with our experimental observations. Therefore, we present a new model of cathodic corrosion, which is based on the assumption that metal anions are formed at the electrode surface during the corrosion process. These anionic species function as precursors for theformation of the final product of cathodic corrosion–metal nanoparticles.